Sp3 bonded 2-dimensional allotrope of carbon: A first-principles prediction. (May 2019) - Sen, Dipayan; Das, Bikram Kumar; Saha, Subhajit; Roy, Rajarshi; Mitra, Anuradha; Chattopadhyay, Kalyan Kumar
Abstract: 2-dimensional allotropes of carbon have lately attracted significant research interests owing to their unique electronic and structural properties. Such sp and sp 2 bonded atomic systems, i.e. graphdiyne and graphene are well represented in the forefront of theoretical and experimental chemistry. However, no stable sp 3 bonded 2-dimensional all-carbon atomic structure has been identified yet. To this end, using state-of-the-art theoretical calculations, we considered cyclobutane motifs, and investigated whether a sp 3 bonded 2-dimensional carbon allotrope could be achieved by assembling ladderane chains. Energetic and dynamic stability studies yielded two such promising structures: one with 4-coordinated carbon atoms and a relatively more stable structure with a combination of 3 and 4-coordinated carbon atoms; both having puckered geometries and partially sp 3 C-C bonds. However thermal stability investigations indicated only the lower energy configuration could be stable at ambient temperature and pressure. The higher energy structure was found to be metastable and was observed to suffer phase-transitions towards the lower energy structure or other stable 2-dimensional allotropes of carbon under exposure to ambient conditions. Investigation of electronic properties of these proposed materials revealed them to be direct-gap semiconductors with small bandgaps, and their tunability by applying external strain implied wide scope of applications. Graphical abstract: Image 1